Dinámicas y estrategias alimentarias instauradas en hogares de Medellín (2014)
ABSTRACT: To understand the family dynamics food in household beneficiaries of supplementary food programs of Medellin such as food consumption strategies introduced in times of food shortages and in the role assumed by women in family feeding. Methodology: the approach was qualitative and the method was focused ethnography. Data was collected through techniques such as individual interviews, group interviews and participant observations. Results: the following are some of the main mechanisms implemented in the households benefiting from supplementary food programs to keep consumption at the usual levels: making preparations with foods that are available at home, serving smaller portions, consuming cheap, tasty and easy-to-prepare foods more often, taking only one drink throughout the day and reducing the number of meals per day. Similarly, it was observed that it is usually the woman who takes the lead role in preparing, obtaining and serving food at home. Likewise, women give priority to feeding children, and they consume the lowest amount of food at home.